Effects of workpiece preheating on surface roughness, chatter and tool performance during end milling of hardened steel D2 - Amin, A. K. M. Nurul; Dolah, Shuriani; Mahmud, Marlina; Lajis, M. A. (Elsevier, 2008)
This paper presents the results of experimental investigations conducted on a vertical machining centre (VMC) to ascertain the effectiveness of brazed circular polycrystalline cubic boron nitride (PCBN) inserts in end milling of hardened steel AISI D2 (60–62 HRC), under room temperature and workpiece preheated conditions. Comparison was made in terms of intensity of chatter, chip formation instability, tool wear and metal removal capacity of the tool and surface roughness of the machine parts. It has been found that chips formed are composed of primary and secondary serrated teeth and their formative frequencies have definite relationship with the chatter frequencies. Though initial average flank wear of the tool during preheated machining is found to be slightly higher compared to that of room temperature machining, the extrapolated tool life appears to be higher in the case of preheating. The main mechanisms of tool failure are found to be superficial plastic deformation, diffusion and notching. It has been observed that feed per tooth, cutting speed, preheating and amplitude of chatter have direct bearing on the surface roughness. It has been observed that preheated machining of the material leads to surface roughness values well below 0.4_m, such that the operations of grinding as well as polishing can be avoided at the higher cutting speeds.